EFEKTIVITAS PELAYANAN PERUSAHAAN DAERAH AIR MINUM DI KAWANGKOAN UTARA KABUPATEN MINAHASA - MANITIK, ROLANDO; Rares, Joyce Jacinta; Ogotan, Martha (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT: Water plays an important role in human life, animals, plants and other bodies. The water weneed is water that meets the requirements of good health, physical requirements, chemical, bacteriologicaland radioactive. Uncontaminated water is defined as water that does not contain a specific foreignsubstances in quantities exceeding the limits set so that the water can be used normally. General conditionsfaced Water District Kawangkoan North in connection with customer service that is the difficulty ininstallation or connection to a public that has been registered but has not been connected or has not receivedinstallation, as well as the distribution of water that sometimes substandard home-home customer. As forthe purpose of this study was to determine how the effectiveness of local water companies in North MinahasaDistrict Kawangkoan.The method of this research is qualitative research methods and data collection techniques in this study isthe observation / observation localized research, conduct interviews, and documentation. The researchshows that there are some constraints in the service of the Regional Water Company office in NorthKawangkoan.Keywords: Effectiveness Service, the Regional Water Company.